PENGARUH BUDAYA ORGANISASI TERHADAP SEMANGAT KERJA GURU MTs. DARUL MUQOMAH PEKANBARU - Yapentra, Arhipen; Novita, Hesti (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
This study aims to determine the influence of organizational culture on the morale of teachers at MTs Darul Muqomah Pekanbaru. Quantitative analysis includes validity and reliability tests, normality tests, hypothesis testing through t-test and analysis of the coefficient of determination (R2). The data analysis technique used is simple regression analysis, which serves to prove the research hypothesis. The results of data processing obtained that hypothesis testing with t test there is a t count of 3.989 and t table of 2.036 so that the hypothesis test in this study is t arithmetic 3.989 > t table 2.036 and also a significance level of 0.00 < 0.05 which means organizational culture significant effect on the morale of teachers MTs Darul Muqomah Pekanbaru. The form of the relationship between organizational culture and the morale of the teachers at MTs Darul Muqomah Pekanbaru is positive, as evidenced by the regression coefficient (b) of 0.517, which means that each increase in organizational culture by one unit will increase the morale of the teachers at MTs Darul Muqomah Pekanbaru by 0.517 units. The value of R Square is 0.332. It means that the contribution of organizational culture to the morale of the teachers at MTs Darul Muqomah Pekanbaru is 33.20%. While the remaining 66.80% is influenced by other variables not included in this study.